A preliminary note on core reduction methods at the open-air site of vadopampa, ayacucho, Peru - Pérez A. (2017)
I would like to thank Edwin Silva, teacher and friend, who has always been very generous. Many thanks also to Leslye Valenzuela for her patience and comments. Thanks also go to: Mr. Grobel Irupaiya Canales, Lacayan, who hosted us at Incuyo; Mr. Wilver Benitez Diestro, mayor of the Puyusca district, for his collaboration in transportation and logistics; Carlos Rengifo, for his help in the English version of this manuscript; and Dr. Frederick Foulds, for his patience. This research was funded by the Consejo Nacional de Ciencia,Tecnología e Innovación Tecnológica (CONCYTEC), through Cienciactiva.